Elementary survival strategy: first record of death-feigning behavior in Atractus pantostictus (Colubridae, Dipsadinae) - Alexandre, César; Souza, Allan; Muscat, Edelcio (Herpetologia Brasileira, 2026)
This study reports the first record of primary (crypsis) and secondary (behavioral) defensive strategies in a snake of the genus Atractus. During fieldwork conducted in Santana da Vargem, Minas Gerais, southeastern Brazil, a death-feigning (thanatosis) behavior was observed in an individual of Atractus pantostictus. The event allowed the documentation of a sequence of defensive responses exhibited by the snake. When gently touched, the individual initially remained motionless, then performed body contortions, and finally coiled its trunk while simulating death. The entire behavioral sequence lasted approximately twenty seconds and was followed by escape. This record expands the knowledge of defense mechanisms in fossorial species such as A. pantostictus. It contributes to the understanding of antipredator behaviors in the genus Atractus, whose natural history remains poorly known.